Pertumbuhan dan Hasil Beberapa Varietas Tanaman Padi (Oryza sativa L.) pada Tingkat Kondisi Kekeringan - mawardi majid (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
Abstract. This research aims to know the growth and yield of some varieties of rice plant on the level of drought conditions. Implemented in a plastic garden House experiments Faculty of Agriculture University of Syiah Kuala in September 2015 – January 2016. The design used in this research is the design of Swath (RPT) is divided into 3 x 3 i.e. 3 repeats the experiment, with three levels of drought, namely K0 = 0, K1 =-35 and K2 =-70 kPa equivalent to K0 = 0, K1 =-0.35, K2 =-0.70 MPa and 3 varieties that are used i.e. V1 (Situ patenggang), V2 (Sanbei) and V3 (IR64) thus there are 9 combination treatment. The results of this study show that treatment of drought effect on growth and yield of rice plants. Treatment of varieties also have an effect on growth and yield of rice plants, and there is interaction between varieties and drought against the growth and yield of rice, the highest result found in Situ Patenggang varieties. Key words: drought, variety, growth and yield of rice plant